2021
DOI: 10.3390/jfb12020026
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Fabricating the Electrospun Biopolymer-Based Biomaterials

Abstract: Biopolymers formed into a fibrous morphology through electrospinning are of increasing interest in the field of biomedicine due to their intrinsic biocompatibility and biodegradability and their ability to be biomimetic to various fibrous structures present in animal tissues. However, their mechanical properties are often unsatisfactory and their processing may be troublesome. Thus, extensive research interest is focused on improving these qualities. This review article presents the selection of the recent adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 137 publications
(293 reference statements)
0
21
0
Order By: Relevance
“…Similarly, in the previous studies it was found that addition of whey protein increased the viscosity of the electrospinning solution, resulting in the formation of continuous bead-free nanofibers. In these studies, it was discovered that by supporting the whey protein with easily spinnable polymers such as PEO and performing other treatments such as drastically changing the pH of the solutions from their isoelectric point or applying heat treatment, the protein unfolding and amino group release are accelerated, and the molecular entanglement in the polymer solution is increased [9,23,[35][36][37]. The same trend was observed in apparent viscosity.…”
Section: Solution Properties and Their Relation To Fiber Morphologymentioning
confidence: 89%
“…Similarly, in the previous studies it was found that addition of whey protein increased the viscosity of the electrospinning solution, resulting in the formation of continuous bead-free nanofibers. In these studies, it was discovered that by supporting the whey protein with easily spinnable polymers such as PEO and performing other treatments such as drastically changing the pH of the solutions from their isoelectric point or applying heat treatment, the protein unfolding and amino group release are accelerated, and the molecular entanglement in the polymer solution is increased [9,23,[35][36][37]. The same trend was observed in apparent viscosity.…”
Section: Solution Properties and Their Relation To Fiber Morphologymentioning
confidence: 89%
“…69,228 Also, some of the biopolymers are completely insoluble in organic solvents and others, like collagen, can be irreversibly damaged as their structure can be permanently denatured resulting in a much lower level of applicability than originally expected. 229 It is critical to developing green electrospinning techniques, such as utilizing non-hazardous solvents or enhancing machinery performance to cut back on dangerous gas emissions. Deep eutectic solvents (DES) have recently gained popularity as non-volatile, safe substitutes for organic solvents in electrospinning employed nanofabrication.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…Moreover, hexafluoro-2-propanol and 2,2,2-trifluoroethanol can be used for collagen dissolution, leading to an improvement in solution electrospinnability, but also to the alteration of collagen structure. 86…”
Section: Polymers Used For Curcumin-loaded Fiber Formationmentioning
confidence: 99%
“…Moreover, hexafluoro-2-propanol and 2,2,2-trifluoroethanol can be used for collagen dissolution, leading to an improvement in solution electrospinnability, but also to the alteration of collagen structure. 86 Thus, Mohammad Ali Ghavim et al 87 obtained the bone regeneration membranes based on collagen with the addition of curcumin and aspirin-loaded PLGA nanoparticles. Membranes prepared demonstrated both the retention of surrounding soft tissue from bone defects, and high antibacterial effect with bone healing activity generated by curcumin.…”
Section: Materials Advances Reviewmentioning
confidence: 99%